Seasonal Occurrence of Greater Banded Hornet (Vespa tropica Linn.) in Western Honey Bee (Apis mellifera Linn.) Colonies under Terai Agro-ecological Region of West Bengal - Singha, Sibananda; Saha, Samrat; Nath, Riju; Kalla, Pushpa; Laskar, Nripendra; Pal, Suprakash (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during September, 2018 to August, 2020 on the seasonal incidence of Vespa tropica Linn. on Apis mellifera Linn. under terai agro-ecological region of West Bengal, India. Ten numbers of A. mellifera colonies of similar strength was placed in the apiary unit of Uttar Banga Krishi Viswavidyalaya, West Bengal, India in which no pest management strategies were carried out. Incidence of V. tropica was recorded higher during July to October peaking in the month of July (251.50±22.17 visits day-1) with annual average success rate of 57.23%±1.16%. From December to March little or no incidence was recorded. Minimum abundance of hornets was recorded at 07:00–09:00 hours. After that incidence started increasing with maximum incidence recorded at 13:00–15:00 hours i.e., 43.52±11.97 visits to the bee colonies day-1 during this time gap. Both maximum and minimum temperature and relative humidity showed significantly positive correlation with the incidence of V. tropica. However, rainfall was found to be detrimental for their incidence as it showed negative and non-significant correlation with their incidence. As V. tropica has been considered as a major enemy of honey bees, so the results obtained from the study can be used for designing integrated pest management strategies against this pest that will allow the beekeepers to focus on that particular time period when this pest is more abundant.